Formation of Professional Identity in Pediatric Residents Working in Military Hospitals - Arshad Khushdil, Shahzad Hussain Waqar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Professionalism is one of the basic attributes of a doctor patient relationship. During development of professional identity, doctors interact with their community which provides opportunity for mutual negotiation of identity and they keep improving their abilities. The development of this professional identity is a difficult skill indoctors working in Military hospitals. Aim: To explore development of Professional Identity in doctors working in pediatrics department of military hospital. Study design: Qualitative study based on phenomenological design. Place and duration: The study was conducted in Combined Military Hospital Quetta from Jan 2022 to June 2022. Methodology: All doctors serving in uniform in paediatrics department were included.In depth interviews were taken, recorded, transcribed and anonymized. Data interpreted manually, common themes originating from interviews were analysed and results formulated. Results: Six themes were found from transcript. Participants discussed about their professional life during service in military and road to gain professional excellence. Conclusion: Military residents working in paediatrics department have dual roles of serving the nation during peace as well as war and natural disasters. Keywords: Professionalism, Professional Identity, Paediatrics, Military.